Os movimentos do silêncio: espelhos de Jorge Luís Borges - Villarta-Neder, Marco Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
This thesis undertakes a reflection on the silence in relation to the production of the senses, using as corpus literary texts of Jorge Luís Borges, related to the thematic of the mirror, metaphor used in this work to represent the silent path of the movement of the meanings. The silence is assumed here in two categories: (1) absence, that represents the non-saying, and (2) excess, which represents the superposition that the word establishes on the silence or on other words. Those dialectic and complimentary relationships with the silence, more than a deletion of the voices of the discourse, is a procedure of establishment of the heterogeneity. Sustained in the Discourse Analysis of French line, the process of constitution of the meanings was discussed as movement, of which participate, silence(s), the word and the dialectic relationship among them. The work's objectives are the following: (a) to identify and to discuss the existence of indications (internal and/or external to the text) that send the reader for the silence; (b) to discuss relationships among metaenunciative operations, intertextual relationships and the written text; c) in the universe of selected texts of the borgean production, to point out some specificities of the literary writing text while specific configuration of silence(s) as procedures of establishment of shown heterogeneity. They were still discussed the relationships among silence, authorship and the author's and the reader's functions, aspects directly linked to the conceptions and to the aesthetic of the borgean work. Related to this last one, they were characterised as a dialectic game between diversities of silences, heterogeneous, and the relationship of these with the word.

Esta tese empreende uma reflexão sobre o silêncio em relação à produção dos sentidos, tendo como corpus textos literários de Jorge Luís Borges, voltados para a temática do espelho, metáfora utilizada neste trabalho para representar a trajetória silenciosa do movimento dos sentidos. O silêncio é aqui assumido em duas categorias: (1) ausência, que representa o não dizer, e (2) excesso, que compreende a sobreposição que a palavra instaura sobre o silêncio ou sobre outras palavras. Essas relações dialéticas e complementares fazem do silêncio, mais que um apagamento das vozes do discurso, um procedimento de instauração da heterogeneidade. Sustentada na Análise do Discurso de linha francesa, discutiu-se o processo de constituição dos sentidos como movimento, do qual participa(m), o(s) silêncio(s), a palavra e a relação dialética entre eles, tendo como objetivos: (a) Identificar e discutir a existência de indícios (internos e/ou externos ao texto) que remetam o leitor para o silêncio; (b) discutir relações entre operações metaenunciativas, relações intertextuais e o texto escrito; c) no universo de textos selecionados da produção borgeana, apontar algumas especificidades do texto literário escrito enquanto configuração específica de silêncio(s) como procedimentos de instauração de heterogeneidade mostrada. Discutiram-se ainda as relações entre silêncio, autoria e funções do autor e do leitor, aspectos diretamente ligados às concepções e ao fazer estético da obra borgeana. Quanto a esta última, buscou-se caracterizá-la como um jogo dialético entre diversidades de silêncios, heterogêneos, e a relação destes com a palavra.
Keywords: Borges, Jorge Luis 1899-1986 Crítica e interpretação; Análise do discurso literário; Linguagem - Filosofia; Silêncio na literatura; Sentido (Filosofia); Discourse analysis